Energy imbalance gap was associated with body mass index and sex in Latin American adolescents—results from the ELANS study - Hernandez, Pablo; Herrera-Cuenca, Marianella; Ferrari, Gerson; Yépez Almeida, Rafaela; Yépez García, Martha Cecilia; Villar Cáceres, Mónica; Cortés Sanabria, Lilia Yadira; Sifontes, Yaritza; Landaeta-Jimenez, Maritza; Gómez, Georgina; Monge-Rojas, Rafael; Pareja, Rossina G.; et al. (Frontiers in Nutrition, 2024)
Introduction: Energy imbalance gap (EIG) is defined as the average daily difference between energy intake (EI) and energy expenditure (EE). This study aimed to examine the associations between EIG and sociodemographic and anthropometric variables in the adolescent population of eight Latin America countries. Methods: A total of 680 adolescents aged 15 to 18 were included in this study. The estimation of EI was based on two non-consecutive 24-hour dietary recalls. EE was predicted from Schofield equations using physical activity level obtained through the long version of the International Physical Activity Questionnaire. Sociodemographic data and anthropometric measurements were also obtained. A descriptive analysis and multilevel linear regression models were used to examine associations between variables. Results: The mean EI, EE, and EIG were 2091.3 kcal, 2067.8 kcal, and 23.5 kcal, respectively. Argentina had the highest EI and EIG, whereas Chile had the lowest EI and EIG. Males had a higher EI (2262.4 kcal) and EE (2172.2 kcal) than females (1930.1 kcal and 2084.5 kcal), respectively (p<0,05). Overweight subjects had a lower EIG than did underweight and normal-weight subjects (p<0,05). Subjects with low socioeconomic status (SES) had a lower EE (2047.0 kcal) than those with a high SES (2164,2 kcal) (p<0,05). Conclusion: Sex and BMI were associated with EIG in adolescents from Latin America.